Refining minimal engineered receptors for specific activation of on-target signaling molecules - Masashi Miura; Masahiro Kawahara (Scientific Reports)
Abstract Since designer cells are attracting much attention as a new modality in gene and cell therapy, it would be advantageous to develop synthetic receptors that recognize artificial ligands and activate solely signaling molecules of interest. In this study, we refined the construction of our previously developed minimal engineered receptors (MERs) to avoid off-target activation of STAT5 while maintaining on-target activation of signaling molecules corresponding to tyrosine motifs. Among the myristoylated, cytoplasmic, and transmembrane types of MERs, the cytoplasmic type had the highest signaling efficiency, although there was off-target activation of STAT5 upon ligand stimulation. Tyrosine-to-phenylalanine ​​mutagenesis revealed that both the tyrosine motif for recruiting target signaling molecules and the tyrosine residues in the JAK-binding domain did not contribute to off-target activation of STAT5. Using alanine mutagenesis for Box1 of the JAK-binding domain of MERs, we ultimately found a Box1 mutation that slightly reduced activation of on-target signaling molecules but minimized off-target activation of STAT5. The refined MER enabled us to precisely analyze the signaling and cell fate-inducing properties of seven tyrosine motifs. Therefore, the refined MER, which realizes activation of on-target signaling molecules with high signal-to-noise ratios, will attract much attention as a tool for functionalizing designer cells and more broadly in the field of synthetic biology.